Effectiveness of the Free Nutritional Meal Program on Junior High School Students’ Nutritional Status in Palembang City - Ammar Januar; Meirizal Usra; Reza Resah Pratama (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
School meal programs may improve students’ access to nutritious food, yet implementation quality and short-term anthropometric outcomes do not necessarily move at the same pace. This study evaluated Indonesia’s Free Nutritious Meal Program in two public junior high schools in Palembang and examined changes in students’ nutritional status. A comparative program-evaluation design was used, guided by the Context, Input, Process, and Product model. Participants were 133 students (66 from SMP Negeri 13 and 67 from SMP Negeri 1), 20 teachers, and 27 parents. Data were obtained through observation, questionnaires, interviews, documentation, and body-mass-index-for-age assessment. Descriptive statistics summarized implementation and stakeholder perceptions, while paired-samples t-tests assessed pre–post differences. Observation scores reached 100% for all four evaluation components in both schools. Stakeholder ratings were also favorable: 78.4% among students, 80.8% among teachers, and 80.2% among parents. The number of students in the normal nutritional-status category increased from 40 to 53 at SMP Negeri 13 and from 46 to 54 at SMP Negeri 1. However, the reported paired tests were not statistically significant in either school (p = .320). The program was therefore operationally effective, but the available short-term data did not establish a significant anthropometric effect. Its principal contribution is showing why implementation performance and health outcomes should be evaluated as related but distinct dimensions. Longer exposure, repeated anthropometric measurement, and control of household diet, attendance, and physical activity are required for a stronger estimate of impact.